A lightweight localized high-concentration ether electrolyte for high-voltage Li-Ion and Li-metal batteries. (1st June 2022) - Peng, Xudong; Lin, Yanke; Wang, Yu; Li, Yiju; Zhao, Tianshou
Abstract: The emerging localized high-concentration electrolytes (LHCEs) with small salt dosage, low viscosity, and favorable electrode wettability have triggered extensive research interest recently. However, so far, it is still challenging to develop an LHCE that has both superior anode compatibility and high voltage stability, as well as low density and low cost to construct high specific energy batteries. In this work, we propose an anode-compatible and high-voltage (up to 4.7 V) ether-based LHCE by introducing the cost-efficient (~0.385 $ g −1 ) and lightweight (1.19 g cm −3 ) benzotrifluoride (BTF) as a diluent (BTF-LHCE). Benefitting from the unique solvation structure and interfacial chemistry of the BTF-LHCE, ultrahigh average Coulombic efficiency (CE) can be achieved in the BTF-LHCE system both for the Si (99.83%) and metallic Li anodes (99.45%). Notably, the assembled Si||NCM622 and Li||NCM622 pouch cell based on our designed BTF-LHCE can realize high cell-level specific energy densities of 257.4 and 349.4 Wh kg −1, respectively, which are among the best values reported. This study provides a promising strategy to develop advanced ether-based electrolytes towards large-scale applications of high-voltage and high-specific-energy battery technologies. Graphical Abstract: High Si or Li anode stability and high oxidation voltage are simultaneously achieved in the localized high-concentration electrolyte containing the low-cost and lightweight benzotrifluoride (BTF). High energy densities up to 350 Wh kg −1 can be achieved by coupling NCM 622 cathode and Li-metal/Si anodes in the designed electrolyte. ga1 Highlights: A new low-cost and low-density diluent of BTF is proposed for ether-based localized high concentration electrolytes (LHCE). The BTF-LHCE is highly compatible with the Si/Li anode, and has high oxidation voltage. The BTF-LHCE enables high specific energy densities in the Si-based or Li-metal batteries.